ANALYSIS OF PROFIT INCREASE THROUGH OPTIMISATION OF PRODUCTION COSTS AND SELLING PRICE OF EUCHEMA COTTONII SEAWEED - Alamsa Alam; Mappa Panglima Banding; Riyans Ardiansyah; Herman Herman; Olivia Pamilangan Andi’lolo (RISTANSI: Riset Akuntansi, 2026)
This study aims to analyze financial statements and evaluate the financial performance of PT Sebatik Jaya Mandiri, a seaweed (Eucheuma cottonii) export company, using financial ratio analysis. This research employs a descriptive quantitative approach with financial statement analysis techniques including horizontal analysis, vertical analysis, and financial ratio calculations. Data were obtained from the company's 2025 financial reports, encompassing the statement of financial position, income statement, and operational data. The analysis results indicate that the company demonstrates healthy financial performance with a gross profit margin of 39% relative to sales revenue. Profitability ratio analysis reveals that the company is capable of generating adequate profits from total assets and equity, with competitive return rates. The company's financial structure shows a good balance between the use of equity and external financing in supporting operational activities. These findings support signaling theory, which emphasizes the importance of accurate financial information in stakeholder decision-making. The company is recommended to maintain financial reporting transparency and enhance operational efficiency through more optimal production cost control. This study contributes by integrating financial ratio-based financial statement analysis in the seaweed industry, which has rarely been examined from a financial accounting perspective.